Methods of processing gaharu green, yellow and black tea - Shuhaimi, Muhammad Asyraf (2019)
In Malaysia, Aquilaria tea is also known as Gaharu tea. Due to long period of time for a single gaharu tree to induction and growth, farmers wanted to sustain their living by seeking into opportunities such as processing tea derived from the abundant gaharu leaves in the plantation. However, there is no formal method in processing gaharu tea in the market. Currently, there are three type of tea that can be produced through different processing method mainly by varying the degree of fermentation of each method which result in green tea, yellow tea and black tea. The aim of this research is to process gaharu leaves into gaharu green, yellow and black tea and to study the content from each tea which is antioxidant and caffeine. Fermentation is said to have effect on the caffeine and antioxidant on plant-based food. Thus, analysis of caffeine on each gaharu tea was done by using elemental analyzer to study the composition of nitrogen since caffeine is mainly composed of nitrogen atoms. Based on the result obtained, the nitrogen composition is the highest in black gaharu tea compared to gaharu yellow and green tea indicating highest caffeine. Compared to market tea derived from leaves of Camillia sinensis, caffeine content in gaharu tea is lower. Furthermore, the analysis of antioxidant was done using DPPH assay method. The result showed that antioxidant content is higher in fermented black and yellow gaharu tea compared to green gaharu tea. When comparing to standard commercial BOH green and black tea BOH, gaharu tea has lower antioxidant content. Fermentation is said to increased antioxidant activity by releasing greater amount of flavonoid contained in the leaves.